Al-Uslūb al-Taqābulī fī Sūrah al-Baqarah wa Dilālatuhu - Anisa Rosi Oktaviana (Arabic Language and Letters Department, 2020)
The purpose of this study is to explain and identify the conflicting meanings in Arabic. It refers to the Muqabalah Theory in Balaghah, and At-Tadzat in Semantics using Ali Al-Khouli’s opinion, there are also different patterns of sentence contradiction, which justifies the importance of this study. The data were obtained from AL-Qur'an Surah Al-Baqarah. This research employs a descriptive qualitative method. In Balaghah At-Taqabuly or Al-Muqabalah is a sequence of contradictory meanings; while in the Semantics, it is called At-Tadzat which literally means Antonym. In line with the At-Taqabuly or Al-Muqabalah, it has no special division. But in semantics, there is a difference between the old meaning and the new meaning. In the old meaning, At-Tadzat is interpreted as a different word but has the same meaning, and conversely Ali Al-Khouli interpreted At-Tadzat as 2 opposing words which are the understanding of At-Tadzat in a new meaning. At -Tadzat is divided into 9 parts: 1) Al-Had, 2) Al-'Aks, 3) Al-Mutadarrij, 4) Al-Imtidadi, 5) Al-'Amudy, 6) Al-Juz'i, 7) Al -Dairi, 8) Al-Rutbi, 9) Al-Intisab. In this study only found 5 types of At-Tadzat namely Al-Had, 2) Al-'Aks, 3) Al-Mutadarrij, 4) Al-Imtidadi, 5) Al-'Amudy. The study found 10 syntactic patterns of meaning opposition of the Surah of Al-Baqarah, Ism Maushul, Idhofah, Jar Majrur, Anwa 'Al -otal, Maf'ul bih, Ism Inna, Na't wa Man'ut, At-Tamyiiz, Al-Hal, and Muabtada wa Khabar